Fibroblast Growth Factor 21 Levels Exhibit the Association With Renal Outcomes in Subjects With Type 2 Diabetes Mellitus - Chang, Li-Hsin; Chu, Chia-Huei; Huang, Chin-Chou; Lin, Liang-Yu (Frontiers in Endocrinology, 2022)
Background Whether microalbuminuria predict renal outcomes in patients with type 2 diabetes (T2DM) is argued. Fibroblast growth factor 21 (FGF-21) levels were elevated by the pathogenic process of diabetic kidney disease (DKD). The purpose of the study was to evaluate the associations of FGF-21 and renal outcomes in subjects with T2DM. Methods Chinese patients with T2D were enrolled then observed prospectively and FGF-21 levels of baseline were measured. Associations of FGF-21 levels and renal composite events, defined by a drop > 30% of eGFR or worsening category of albuminuria, were evaluated using Cox analysis. Appropriate cut-off value of FGF-21 was mapped by receiver operating characteristic (ROC) curve. Results Among 312 subjects, higher FGF-21 levels were associated with higher risks of renal events in Cox analysis. The area under curve of FGF-21 levels in ROC curve was optimal (0.67, p < 0.001) and the cut-off value of 1.40 pg/dL exhibited the best sensitivity (76.2%) and specificity (53.5%). The frequency of renal composite events was higher in subjects with FGF-21 ≥ 1.40 pg/dL than in others (30% vs. 10%, p<0.001 by log-rank test). The worse renal outcomes predicted by FGF-21 ≥ 1.40 pg/dL were confirmed using adjustments of Cox sequential models (Hazard ratio 2.28, 95% confidence interval 1.23-4.24, p=0.009) and consistent across subjects with different status of baseline characteristics and renal risks. Conclusion FGF-21 levels were proportional to risks of renal events in broad spectrum Chinese T2DM subjects make it a potential biomarker to predict renal outcomes of T2DM.